REGAIN: a randomized controlled clinical trial of oxaloacetate for improving the symptoms of long COVID - Vernon, Suzanne D.; Rond, Candace; Bell, Jennifer; Butler, Brindisi; Isolampi, Sara; Otteson, Annaleah; Phalwane, Pearl; Mower, Samantha; Roundy, Shad; Kaufman, David L.; Cash, Alan B.; Bateman, Lucinda (Frontiers in Neuroscience, 2025)
BackgroundLong COVID is characterized by fatigue, cognitive dysfunction, and other persistent symptoms. This randomized, double-blind, controlled trial evaluated the efficacy of oral oxaloacetate (OAA) in improving fatigue and cognitive function in adults with long COVID.MethodsA total of 69 participants were randomized to receive either 2,000 mg/day of OAA or the control for 42 days. The primary outcome was fatigue reduction, measured by the Chalder Fatigue Questionnaire (CFQ). The secondary and exploratory outcomes included the DePaul Symptom Questionnaire Short Form (DSQ-SF), health-related quality of life (RAND-36), cognitive function (Defense Automated Neurobehavioral Assessment (DANA) Brain Vital), and time upright (UP Time).ResultsNo significant difference in the CFQ-measured fatigue reduction was observed between the groups. However, the OAA group showed significantly greater improvements in the DSQ-SF-measured fatigue and total symptom burden at day 21 of the trial. Cognitive performance improved significantly in the OAA group, with strong correlations between symptom response and cognitive gains. OAA was well tolerated.ConclusionOAA may contribute to earlier improvements in symptom burden and cognitive function in individuals with long COVID. Further studies are warranted.